Spinal Cord Schistosomiasis: Diagnosis, Pathological Features and Treatment. - Khaled Abdeen (Egyptian Spine Association, 2014)
Background Data: Schistosomiasis affects over 200 million people worldwide. Involvement of the CNS is a rare occurrence. Spinal cord involvement is a rare manifestation of schistosomiasis, the conus medullaris being the primary site of spinal involvement. Purpose: We describe the clinical presentation and the MRI findings of spinal cord schistosomiasis in correlation with surgery and histopatholgical findings. Study Design: Clinical case study. Patients and Methods: We report four cases of spinal cord schistosomiasis presented with rapidly progressive paraparesis associated with urinary incontinence. Three patients were males and one was female (mean age 16 years). MRI of the spine demonstrated a diffusely enhancing mass at the conus medullaris with spinal cord edema, in one of the cases, the edema extended to the upper thoracic segment. Results: In all cases, spinal masses were surgically managed through decompressive laminectomy and either biopsy or debulking. Histopathological examination showed a granulomatous inflammation surrounding bilharzial ova with a final diagnosis of spinal cord schistosomiasis. Patients were treated with Praziquantel and oral steroids. They made a remarkable neurological recovery. Conclusions: Spinal cord schistosomiasis inspite its rare occurrence, must be considered in the differential diagnosis of conus medullaris lesions. Accurate diagnosis, through recognition of its MRI appearance, allows early treatment. Better prognosis depends on decompressive laminectomy, oral steroids to abort intense immune reaction surrounding the ova and antibilharzial drug. (2014ESJ055)